Optimization of loss tangent and capacitor size of micro-vacuum dielectric capacitors. Issue 12 (December 2015) - Tam, Wing-Shan; Kok, Chi-Wah; Wong, Hei
Abstract: A compact model of the loss tangent of the vacuum dielectric capacitor (VDC) in terms of the size of the VDC, capacitance, and ratio of the width of the boundary sealant to the width of the top electrode is presented in this paper. It provides an analytical tool to determine the optimal size of a VDC that achieves the desired trade-off between the capacitance and the loss tangent. VDC design example with a particular sealant is fabricated with measurement results presented in the paper to illustrate the effectiveness of the presented method. The presented methodology is general and can be applied for VDCs constructed with other sealant materials.